Evaluation of the efficacy and tolerance of pamidronate in complex regional pain syndrom type 1 - Marie Doussiere; Corentin Besnier; Yannis Hamidou; Claire Jesson; Jean-Marc Sobhy Danial; Olivier Jarde; Patrice Fardellone; Vincent Goëb (Scientific Reports)
Abstract This study aimed to determine whether the delay between symptom onset and treatment initiation, the dose of pamidronate, and bone mineral density (BMD) influence the response to pamidronate treatment in complex regional pain syndrome type 1 (CRPS 1). A retrospective observational study included patients treated with pamidronate between 2013 and 2023. Treatment response was assessed based on symptom regression according to the Budapest criteria at one (M1) and four months (M4) post-treatment. Multivariate logistic regression identified factors associated with response. Among the 255 patients included, 14.5% responded at M1 and 67% at M4. Multivariate analysis showed that post-traumatic (OR 2.75, 95% CI [1.36–5.7], P = 0.0053) or idiopathic etiology (OR 5.47, 95% CI [1.86–18.92], P = 0.0037) compared to post-surgical etiology, and the presence of initial edema (OR 2.39, 95% CI [1.26–4.62], P = 0.0082), were associated with a better response at M4. BMD, treatment delay, and pamidronate dosage were not significantly associated with treatment response. These findings suggest that initial edema is a predictive factor for response to pamidronate in CRPS 1, with syndrome etiology also influencing outcomes. Increasing pamidronate dosage or infusion frequency does not seem to improve therapeutic efficacy.